Field Studies of Butterflies: A Trial for the Establishment of Indices to Evaluate the Seasonal Fluctuations and the Ecological States of Forests in Bangladesh (University Journal of Zoology, Rajshahi University, 2009)
To establish the indices evaluating the ecological conditions of forests in Bangladesh, total number of butterflies counted in 5 observation sites reached 27,805 (76 species, 10 families). Number of butterflies (IND) and species showed bimodal pattern of seasonal fluctuations peaked in April and November-to- December. The values of I(R5) also showed bimodal seasonal fluctuations peaked in January-to-February and July-to-September. The ratios of IND/I(R5) formed a large peak in November. Results indicate that species diversities of butterflies high in March-to-July decreased thereafter, the numbers of butterflies increased toward November in the study area. Key words: Butterfly, seasonal fluctuation, population indices, ecological states Â  doi:10.3329/ujzru.v27i0.1958 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 67-71